The Role of Murshid in Preventing Divorce among Naqshbandiyah Followers in Rokan Hulu Regency - Suhayib Suhayib; Zainal Arifin (Alhurriyah, 2025)
This article explores the spiritual dimension of the Naqshbandiyah order, with its emphasis on harmonious family as an aspect of family law, so broadening the study of Islamic family law, which typically focuses on fiqh (Islamic jurisprudence) to a more sociological and Sufi perspective. The article focuses on the spiritual aspect, which is at the core of the Naqshbandiyah order's teachings, and is crucial in preventing divorce among its followers, particularly in Rokan Hulu Regency, known as the Land of a Thousand Suluk. This study employed a qualitative method with a participatory approach, conducting observations, interviews, and analyzing data in same stages. The study found that the relationship between divorce prevention among Naqshbandiyah congregations in Rokan Hulu Regency can be observed from the position of the murshids in two ways. Firstly, the spiritual  internalization of tareqat trough the murshid spiritual teachings and secondly the murshid's role in mediation. However, the divorce rate among the congregation remains quite high because the internalization of spiritual aspects is not directly related to the household problems faced. In addition, the role of the murshid in preventing divorce is not completely succesfull since unsupported by a comprehensive competency of conflict management. But, this problem can be overcome with the support of traditional leaders.